India's Population Aspects of Quality and control - "Mitra, Ashok" (New Delhi, 1978)
There is enough justification for the assumption that while the family planning programme must be quick ended in pace, other nationwide synergistic social and economic programmes must be intensified simultaneously to obtain greater mileage out of the programmes of population control. Without such concurrent, supportive measures the success of population control as a one-shot measure, operated however vigorously over a short span of time is very likely severely to backfire, as indeed it did in the beginning of 1977.
Keywords: History; ICS as an author; Indian Civil Service